Mailuoshutong pill for varicocele-associated male infertility—Phytochemical characterisation and multitarget mechanism - Lv, Dongfang; Ji, Yun; Zhang, Qian; Shi, Zhuozhuo; Chen, Tengfei; Zhang, Chao; Wang, Xiangyun; Ren, Taotao; Gao, Zhaowang; Zhong, Chongfu (Frontiers in Pharmacology, 2022)
Background: Varicocele (VC) is a relatively common and treatable cause of male infertility. Mailuoshutong pill (MLST), a traditional Chinese patent medicine, is widely used for treating varicose vein disease, but the underlying mechanism of MLST on varicocele-associated male infertility is unclear. Objective: To reveal the phytochemical characterisation and multitarget mechanism of MLST on varicocele-associated male infertility. Methods: The components in MLST were determined using UHPLC-MS/MS. Through network analysis, we constructed the “Drug-Components-Targets-Disease” network and predicted the potential biological functions and signaling pathways of MLST. Finally, the therapeutic effects and potential mechanisms of MLST were discovered by pharmacological experiments. Results: By network analysis, the “Drug-Components-Targets-Disease” network was constructed, 62 components such as apigenin, limonin, kaempferol, and obacunoic acid may be the main active components of MLST for varicocele-associated male infertility, 28 targets such as VEGFA, PIK3CA, AKT1, and MTOR are considered as hub targets, signaling pathways such as HIF-1, Estrogen, PI3K/Akt, and mTOR may be key pathways for MLST against varicocele-associated male infertility. Through pharmacological experiments, we found that MLST ameliorated VC-induced testicular atrophy. Further histomorphology showed that MLST reduced VC-induced damage to testicular spermatogonia and seminiferous tubule, while MLST reduced ROS and MDA levels and increased antioxidant enzymes (GSH, GSH-Px, SOD, and CAT) levels. TUNEL staining and immunofluorescence showed that MLST reduced VC-induced apoptosis in testicular tissue, decreased BAX, and increased BCL2. Western blot results showed that MLST decreased the phosphorylation of PI3K, AKT, and mTOR proteins, and decreased the expression of HIF1α. Conclusion: The phytochemical characterisation and multitarget mechanism of MLST on varicocele-associated male infertility were discovered using network analysis and pharmacological experiments. We verified that MLST can inhibit the activation of the PI3K/Akt/mTOR signaling pathway, reduce the expression of HIF1α, and further attenuate VC-induced oxidative stress and apoptosis in the testis. These findings provide evidence for the therapeutic role of MLST in varicocele-associated male infertility.